Making space for the religious other in practical theology: the need for broadening the discipline beyond traditional paradigms - Schweitzer, Friedrich (Reforming practical theology, 2019)
Religious spaces are changing, recently most visibly through migration. This implies that migration does not only have consequences on a material level, but also in terms of the religious traditions and selfunderstandings of countries or societies as well as religious bodies and individuals. Religious change is not always welcome, but often connected to prejudice, rejection and aggression. What should be the role of practical theology in this context? This article argues for a dual focus. First, it discusses new analytical tasks referring to religious change and reactions to it. Second, it identifies and evaluates strategies for accompanying the processes of religious change. In the past, this task was mainly connected to religious education. In the meantime, it has also become a topic in diaconal and liturgical contexts as well as of pastoral care. More farreaching questions concerning the presuppositions of practical theology still need to be posed.